A Needs Assessment of Self-development According to Teacher Professional Standards for Private School Teachers in Nakhon Pathom - Yanprechaseat, Yuwaree; Paiwithayasiritham, Chaiyos (Journal of Research and Curriculum Development, 2024)
The objectives of this research were 1) to assess and rank the priorities of needs for self-development according to Teacher Professional Standards of private school teachers in Nakhon Pathom Province; 2) to compare sample teachers’ needs for self-development based on status factors. The sample, chosen through two-stage random sampling, was 412 teachers at a private school in Nakhon Pathom. The research tools were questionnaire. Data were analyzed by Mean, Standard Deviation and PNIModified. Major finding was: 1) The average overall (PNIModified) of need for self-development according to Teacher Professional Standards of the sample teachers from a private school in Nakhon Pathom was 0.38. 2) Male teachers had a slightly higher perceived need for self-development according to Teacher Professional Standards than did female teachers. Single teachers had the highest perceived need for self-development according to Teacher Professional Standards. Teachers in most of the age groups had similar perceived need for self-development according to Teacher Professional Standards. Teachers with the highest level of prior education (bachelor’s degree or master’s degree) had a higher perceived need for self-development according to Teacher Professional Standards. Teachers with 6-10 years of teaching experience had the highest perceived need for self-development according to Teacher Professional Standards. Teachers with less than 5 years teaching experience, teachers with 11-15 years teaching experience and teachers with 16-20 years teaching experience.